Pre- and postoperative tricuspid regurgitation in patients with severe symptomatic aortic stenosis: importance of pre-operative tricuspid annulus diameter. (7th March 2017) - Dumont, Claire; Galli, Elena; Oger, Emmanuel; Fournet, Maxime; Flecher, Erwan; Leclercq, Christophe; Verhoye, Jean-Philippe; Donal, Erwan
Abstract: Aims: Secondary tricuspid regurgitation (STR) is commonly found in patients with aortic stenosis and is associated with increased morbidity. The study sought to evaluate the prevalence of pre-operative STR and its progression after surgical aortic valve replacement (SAVR) or transcatheter aortic valve implantation (TAVI). Also, it sought to analyse the predictors of post-operative changes in STR. Methods and results: We prospectively evaluated 116 patients (aged 75.1 ± 9.8 years, predominantly male) who undergo SAVR or TAVI for severe aortic stenosis (AS) from September 2013 to April 2015. Patients with associated valve disease requiring intervention, significant coronary artery disease or left ventricular ejection fraction (LVEF) <50% were excluded. Clinical and echocardiographic data, including TR grade and right ventricular (RV) size and function, were assessed at baseline and at the 1-year follow-up. At baseline, significant TR was documented in 13 patients (11.1%) and non-significant TR was documented in 103 patients (88.9%). Atrial fibrillation (AF) was more prevalent in patients with a tricuspid annulus diameter ≥40 mm ( P < 0.0051). At the 1-year follow-up, the TR grade had improved in 17 patients (14.7%), was unchanged in 68 patients (58.6%) and had worsened in 31 patients (26.7%). Moderate to severe TR was found in 30 patients (25.8%). Tricuspid annulus diameter >40 mm was the only echocardiographic predictor of significant postoperative TR (relative risk (RR) = 2.12 [1.26–3.54], P = 0.004). Right heart function and size were not independent predictors. Conclusion: Significant TR was present pre-operatively in 11.1% of patients. Post-operative progression was observed in 26.7% of patients. Only tricuspid annulus size >40 mm was an independent echocardiographic predictor of moderate to severe TR at the 1-year follow-up.